Undergraduate student engagement in Business Studies learning activities at a South African private university - Finn, S.; Goto, J.; Lautenbach, G. (South African Journal of Higher Education, 2024)
Poor student success and retention remain significant problems in South African higher learning institutions. This cross-sectional study investigated the dimensions of activity-level student engagement in undergraduate Business Studies modules. The social determinant theory (SDT) of motivation frames the study on marginalised students at a private higher education institution who received 60 per cent to 100 per cent funding from a non-governmental organisation to support their educational studies. Two hundred and sixty-four students took part in the survey. Second–order structural equation modelling analysis indicated that in a lecturer autonomy-supportive environment, agentic engagement was the most important element of student engagement at an activity level, followed by cognitive, emotional and behavioural engagement. In addition, parametric analyses using the ANOVA indicated that being a first-generation student and higher student funding had statistically significant influences on agentic and emotional engagement. Findings will assist policymakers and university lecturers foster agentic engagement in learning environments by designing interventions to improve cognitive, emotional and behavioural engagement. The importance of proper funding for impoverished students is highlighted.